Strategi Guru Pendidikan Agama Islam dalam Implementasi Program Pendidikan Karakter untuk Menanggulangi Perilaku Bullying di SMK Batik Sakti 2 Kebumen - Zahidah, Fadhillahzahidah; Eliyanto, Eliyanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
PAI Teacher's Strategy in Implementing the Character Education Program to Overcome Bullying Behavior at SMK Batik Sakti 2 Kebumen. The purpose of this research is to find out the strategy of PAI teachers in implementing the Character Education Program at SMK Batik Sakti 2 Kebumen. This study uses a qualitative approach of the case study type. Data collection in the form of interviews, observations and documentation taken from the principal, PAI teachers, Waka Curriculum and students of SMK Batik Sakti 2 Kebumen. The data analysis techniques are in the form of data reduction, data presentation and conclusion drawn. Based on the results of the research, it can be concluded that the strategy of PAI teachers in implementing character education programs to overcome bullying behavior at SMK Batik Sakti 2 Kebumen, by cultivating habits through religious values and social values strengthening devotion to Allah SWT, Ta'zim to Teachers and Knowledge, Moral Character and Ukhuwah Islamiyah. The habituation strategy that is applied not only in schools but also in dormitories is also implemented by PAI teachers. The methods used are the habituation method, uswatun khasanah (leadership), Mauidotul Khasanah (advice), Lectures and Practice. The influence of the Character Education Program in increasing the capacity of students and preventing bullying behavior at SMK Batik Sakti 2 Kebumen, by doing activities such as: Congregational prayers, the habit of greetings and shaking hands, the habit of praying before and doing activities, the habit of reciting the Qur'an.